Are ecophysiological adaptive traits decoupled from leaf economics traits in wetlands?. (7th April 2019) - Pan, Yingji; Cieraad, Ellen; van Bodegom, Peter M.
Abstract: Wetland plants have developed a suite of traits, such as aerenchyma, radial oxygen loss and leaf gas films, to adapt to the wetland environment characterised by, for example, a low redox potential and a lack of electron acceptors. These ecophysiological traits are critical for the survival and physiological functioning of wetland plants. Most studies on these traits typically focus on a single trait and a single or few species at the time. Next to these traits, traits of the leaf economics spectrum (LES) that reflect resource acquisition and allocation in plant species have also been frequently measured in wetlands. However, the performance of the LES has rarely been examined among wetland plants. Both suites of traits are critical for—but affect different aspects of—wetland plant functioning and survival. The interactions between them, potentially causing synergies or trade‐offs, reflect wetland plant strategies to simultaneously deal with stress tolerance and resource utilization, and have ramifications for the functioning of wetland ecosystems. Based on a literature review and quantitative analysis of available data, we provide evidence suggesting that LES and ecophysiological traits may be decoupled (e.g., for root porosity and radial oxygen loss vs. leaf nitrogen) or coupled (e.g., for iron tolerance vs. specific leaf area) in wetlands, depending on the trait combination concerned. This rather complex relationship between wetland adaptive traits and LES traits indicates that there can be multiple mechanisms behind the strategies of wetland plants. We further illustrate how adaptive and LES traits together contribute to wetland ecosystem functions, such as denitrification and methane emission. We highlight that both suites of traits should be considered simultaneously when applying trait‐based methods to wetland ecology. Abstract : Plain Language Summary 中文摘要: 湿地植物发展出多种适应性状，其中包括：通气组织、根系泌氧以及叶片气膜等，以专门应对湿地中特有的氧化还原电位低、电子受体缺乏等不利环境胁迫。这些适应性状对于湿地植物的生存及生态生理功能极为重要。之前关于湿地植物适应性状的研究却一般限于一次观测单个或几个物种的某一性状。另一方面，在湿地植物研究中常常被测量的"叶经济型谱"性状反映了植物资源获取和分配策略。但是整个"叶经济型谱"是否在湿地生境中同样存在，仍然未知。这两类性状在湿地植物的功能和生存的不同侧面起到至关重要的作用。这两类性状之间的关系不仅反映了湿地植物对于环境胁迫耐受以及资源利用的策略，而且对于湿地生态系统的功能有着不同方面的贡献。通过文献综述和对于所掌握数据的分析结果表明，这两类性状之间的关系比较复杂，因性状种类的不同可能既存在正交（orthogonal），也存在权衡策略（trade‐offs）。这说明湿地植物对于环境胁迫、资源利用可能存在着复杂的应对策略和适应机制。我们进一步阐述了湿地适应性状和"叶经济型谱"性状是如何共同参与包括脱氮、甲烷生产等湿地生态系统功能的。并以此强调未来在将基于性状的研究方法运用到湿地生态系统的时候，两类性状都应该受到足够的研究及重视。 A plain language summary is available for this article.